The Relationship Between Indirect Aggression and Loneliness for Emerging Adults: What Does Interpersonal Competence Have to Do with Wellbeing? - Di Stasio, Maria; Rinaldi, Christina; Sciaraffa, Jessica; Cheong, Clarissa (Alberta Journal of Educational Research, 2020)
The present study investigated the mediating role of interpersonal competence in the relationship between indirect aggression and loneliness for emerging adults. One hundred and sixty-seven Canadian undergraduate students aged 18-25 participated and completed an anonymous, online survey. Structural equation modeling was used to analyze the mediating role of interpersonal competence in the relationship between indirect aggression and loneliness. The findings revealed that interpersonal competence mediated the relationship between indirect aggression for targets and loneliness. These findings have implications for mental health researchers and practitioners and can inform the development of prevention and intervention programs for young adults dealing with indirect aggression. Keywords: indirect aggression, emerging adults, interpersonal competence, loneliness, psychosocial functioning La présente étude porte sur le rôle de médiation de la compétence interpersonnelle dans le lien entre l’agression indirecte et le sentiment de solitude chez les adultes émergents. Cent soixante-sept étudiants canadiens de premier cycle et âgés de 18 à 25 ans ont complété un sondage anonyme en ligne. Nous avons eu recours à la modélisation par équation structurelle pour analyser le rôle de médiation de la compétence interpersonnelle dans le lien entre l’agression indirecte et le sentiment de solitude. Les résultats indiquent que la compétence interpersonnelle joue un rôle de médiation dans le lien entre l’agression indirecte et le sentiment de solitude. Ces résultats ont des implications pour les chercheurs et les praticiens en santé mentale et ils peuvent contribuer à l’élaboration de programmes de prévention et d’intervention visant les jeunes adultes aux prises avec l’agression indirecte. Mots clés : agression indirecte; adultes émergents; compétence interpersonnelle; sentiment de solitude; fonctionnement psychosocial